Ancient Futures: Learning From Ladakh - Helena Norberg-Hodge; NORBERG-HODGE (Helena) (San Francisco Sierra Club Books, 1991)
u
Keywords: Communities; Rural Development Projects; Rural Conditions; India-Ladakh